2002
DOI: 10.1080/1606635021000041753
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Self-Administration in Animals: A Reevaluation

Abstract: Nicotine self-administration in animals is often viewed as compelling evidence that nicotine is reinforcing to animals and as corroborating the widely accepted thesis that nicotine is a major cause of smoking. This review examines the studies of nicotine self-administration in animals in the past two decades, focusing on threats to the internal and external validity of these studies and on the extent to which they support the thesis that nicotine is reinforcing in animals. The review shows that nicotine self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 144 publications
(196 reference statements)
0
13
1
Order By: Relevance
“…Hence, given their current position that the VS is a primary reinforcement, the statement that nicotine self-administration in the above study was dependent on it being response-contingent "in the absence of other reinforcing stimuli" is inexplicable. Just as puzzling is the authors' claim, based on the same study, that nicotine at a dose of 0.03 mg/kg only increases self-administration when contingent on lever press, which is a finding the authors themselves failed to replicate, both in the present study and in a previous one (Donny et al 2000; see discussion in Dar and Frenk 2002).…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…Hence, given their current position that the VS is a primary reinforcement, the statement that nicotine self-administration in the above study was dependent on it being response-contingent "in the absence of other reinforcing stimuli" is inexplicable. Just as puzzling is the authors' claim, based on the same study, that nicotine at a dose of 0.03 mg/kg only increases self-administration when contingent on lever press, which is a finding the authors themselves failed to replicate, both in the present study and in a previous one (Donny et al 2000; see discussion in Dar and Frenk 2002).…”
contrasting
confidence: 56%
“…The possibility that light may act as an unconditional reinforcement in nicotine self-administration studies was explicitly discussed in our critique of the nicotine addiction thesis (Frenk and Dar 2000, p. 62) and again in our review of animal self-administration studies (Dar and Frenk 2002). [Incidentally, as Donny and one of his co-authors for the present article reviewed our book (Donny et al 2002), their failure to cite it is puzzling.]…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…However, a separate experiment in which nicotine was administered to the monkeys at the same speeds used in the self-administration procedures showed that infusion speed and plasma nicotine levels were highly correlated (r=0.74; p<0.01). As higher blood levels of nicotine can lead to increased level pressing because of general activation (Dar and Frenk 2002), this confound undermines the attribution of increased level pressing to reinforcement by fast delivery of nicotine. West et al (2000) compared the abuse liability and dependence potential of four NRTs as follows: nicotine gum, patch, spray, and inhaler.…”
Section: Is Nicotine's Speed Of Delivery Related To Reinforcement?mentioning
confidence: 98%
“…Here, we highlight some of the evidence for our hypothesis and explain why behavioral activation does not adequately account for the available data. Before presenting these data, we want to identify clearly the alternative hypothesis Frenk and Dar are proposing Dar 2000, 2003;Dar and Frenk 2002). They suggest that lever pressing is a consequence of prior food training and/or non-drug stimuli that either act as unconditioned reinforcers, or conditioned reinforcers (as a consequence of their pairing with food).…”
mentioning
confidence: 97%